2013
DOI: 10.2355/isijinternational.53.866
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Primary Scale Formation and Descalability on Steels Containing Ni and Ni+Si

Abstract: Nickel and silicon are attractive alloying elements for high-strength low-alloyed (HSLA) steel production. However, it is well known that the presence of Ni and Si in the steel can impair the surface quality, making it unsuitable for certain markets. The combined effects of Ni+Si on the oxide scale formation are still relatively unknown. Literature is dealing mostly with steels containing combinations of Ni and Si, with either traces of nickel (0.1%) or very high (8-16%) nickel levels. At Tata Steel we explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…The largest differences were found between the inner oxidation zone metallic area compositions of the low to medium boron additions and the high boron addition. Based on previous study regarding scale entanglement with the metal substrate, it was observed that the presence of metal‐free fracture paths throughout the scale layer is favorable to descaling and the presence of oxide “pegs” protruding into the metal substrate at the scale‐metal substrate interface is detrimental to descaling, especially in alloys containing Ni and Si . Based on these results, the more metal‐free zones there are in the inner and intermediate oxidation zones, the easier it is to remove the scale layer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The largest differences were found between the inner oxidation zone metallic area compositions of the low to medium boron additions and the high boron addition. Based on previous study regarding scale entanglement with the metal substrate, it was observed that the presence of metal‐free fracture paths throughout the scale layer is favorable to descaling and the presence of oxide “pegs” protruding into the metal substrate at the scale‐metal substrate interface is detrimental to descaling, especially in alloys containing Ni and Si . Based on these results, the more metal‐free zones there are in the inner and intermediate oxidation zones, the easier it is to remove the scale layer.…”
Section: Discussionmentioning
confidence: 97%
“…Based on previous study regarding scale entanglement with the metal substrate, it was observed that the presence of metal-free fracture paths throughout the scale layer is favorable to descaling [13] and the presence of oxide "pegs" protruding into the metal substrate at the scale-metal substrate interface is detrimental to descaling, especially in alloys containing Ni and Si. [13][14][15] Based on these results, the more metal-free zones there are in the inner and intermediate oxidation zones, the easier it is to remove the Table 3. 1300 8C analysis point compositions of samples 1511L and 1513L in wt%, analysis point origins are denoted in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, removing an oxide scale formed during hot-rolling process on the Ni containing steel by high-pressure hydraulic descaling is known to be difficult. [1][2][3][4] Asai et al 3) evaluated the removability of scale in Ni containing steel. They reported that the scale becomes difficult to be removed if Ni concentration in the steel is as little as 0.05 mass%.…”
Section: Introductionmentioning
confidence: 99%
“…2,3) Correspondingly, wustite (Fe1-xO, with 1-x ranging from 0.83 to 0.95) dominates at high temperatures (normally > 650°C for steels), whereas Fe3O4 prevails at low temperatures, and hematite (Fe2O3) remains low in either case. [17][18][19] The proportion of the three phases within oxide scale at high-temperature oxidation depends greatly on the equilibrium transformation of Fe1-xO or Fe3O4 precipitation which is related to heat treatment, atmospheric conditions and alloying elements in the steel.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Specifically, oxide scale formed in hot strip rolling has posed a serious obstacle, and thereby causes the surface quality of final products to deteriorate. [5][6][7][8] In most cases, many different surface properties of metals and alloys can dominate surface characteristics of two solids in contact and thereby influence tribological performance.…”
Section: Introductionmentioning
confidence: 99%